Peran Sekolah Adat Dalam Melestarikan Kebudayaan Batak Toba Di Desa Sihaporas Kecamatan Pematang Sidamanik - Heriando H. Manik; Masniar Hernawati Sitorus; Martua Sihaloho; Rusmauli Simbolon; Harisan Boni Firmando (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The indigenous people in Tano Batak continue to inherit the culture of their ancestors. Indigenous peoples cannot be lulled by the development of modernization. Currently, society must better protect and preserve the culture passed down by its ancestors so that it is not eroded by the progress of the times. Apart from that, indigenous peoples must also pay attention to the younger generation to serve as their next generation, so it is necessary to establish traditional education as a place of learning to learn more about their history and culture. The method used in this research is a qualitative method, to understand the phenomenon of what is happening in the field. The traditional school in Sihaporas Village has an important role in preserving Toba Batak culture so that the younger generation continues to understand their culture and makes the younger generation the next generation of their parents. So that the customs inherited from their ancestors can be preserved. Parents must also invite their children to follow traditions and all ritual events carried out from ancient times. Because with this traditional education, the younger generation will know more about how important it is to preserve culture